Perancangan Validasi Permohonan Narasumber Pada Sistem Informasi Permohonan Narasumber Menggunakan Finite State Automata - Fadillah Said; Dwi Andriyanto; Retno Sari; Windu Gata (LPPM Universitas Bina Sarana Informatika, 2020)
The Law and Human Rights Research and Development Agency in carrying out its duties and functions provides services in the form of Providing Resource persons. Managing mail manually requires a long time and allows for document loss. This study aims to reduce the use of time, help minimize the loss of letters, and reduce errors in recording letters by storing them in a database in accordance with the specified format. In the design of the system will check the applicant's input and validate before the data is stored in the database using Finite State Automata (FSA) so that the data stored in accordance with the format specified. The implementation of this research is expected to be able to help the Law and Human Rights Research and Development Agency to reduce the use of time, help minimize the loss of letters, and reduce errors in recording letters in accordance with the specified format.